A Typical Basalt Platform Landslide: Mechanism and Stability Prediction of Xiashan Landslide - Yongliang Huang; Zhiwei Sun; Chunyan Bao; Man Huang; Anyuan Li; Minghao Liu (Advances in Civil Engineering)
The Xiashan landslide, which is classified as a typical basalt platform landslide, is the most massive landslide in Zhejiang Province, China. Once sliding occurs, it will pose a severe threat to the life and property of downstream residents and the nearby section of Hangzhou-Taizhou Expressway. On the basis of the geological conditions, present situation, and latest monitoring data of the landslide, this study finds that rainfall is the main influencing factor, and the creep mode is the main prediction mode of its subsequent deformation. The rainfall statistics of the landslide area in the past 30 years show that the rainfall and rainfall frequency in the landslide area display an increasing trend. The probability of heavy rain with rainfall intensity of 100–250 mm/day in the landslide area is very high. On this basis, combined with the numerical analysis method, a finite element model of the slope considering rainfall and groundwater conditions is constructed to analyze the causes and failure mechanism of this landslide comprehensively. Results indicate that the maximum tensile stress at the top of the trailing edge under the natural state is 5.10 MPa, which is very close to the saturated tensile strength of rock mass. Thus, tensile cracks are easily generated and developed, thereby causing the failure mode to be the hydraulic driving type. Also, with the increase in rainfall intensity, the slope plastic strain increases and the slope plastic zone develops and extends until it is completely penetrated. When the rainfall intensity is more than 200 mm/day, the slope safety factor is close to unity, and the slope approaches a failure condition. Therefore, the landslide should be controlled through water treatment and integrated with engineering measures.